2017
DOI: 10.1051/swsc/2017024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spatial variations of the geoelectric field on geomagnetically induced currents

Abstract: -The geoelectric field driving geomagnetically induced currents (GIC) has complex spatial variations. It follows that different patterns of the field vectors in a given area having the same regional mean can produce very different GIC. In this study, we consider a few power grid models and calculate GIC due to a modelled geoelectric field with a regional mean magnitude of 1 V/km. Altogether 8035 snapshots of the electric field are included. We also assume two different ground conductivity models, of which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
(53 reference statements)
1
16
0
Order By: Relevance
“…It is shown that spatial‐scale geomagnetic variations on the order of hundreds of kilometers can result in up to a 60% difference in GICs across a transmission line of 200‐km length. Viljanen and Pirjola (2017) explicitly investigated the effects on similar scales, but from variations in the geoelectric field vector direction instead of magnitude; even so, their results converge on a similar conclusion to ours. That is, accurate modeling of GICs requires that the spatial structure of the geomagnetic variations should be taken into account with the scale of the network.…”
Section: Discussionsupporting
confidence: 85%
“…It is shown that spatial‐scale geomagnetic variations on the order of hundreds of kilometers can result in up to a 60% difference in GICs across a transmission line of 200‐km length. Viljanen and Pirjola (2017) explicitly investigated the effects on similar scales, but from variations in the geoelectric field vector direction instead of magnitude; even so, their results converge on a similar conclusion to ours. That is, accurate modeling of GICs requires that the spatial structure of the geomagnetic variations should be taken into account with the scale of the network.…”
Section: Discussionsupporting
confidence: 85%
“…Fernberg, 2012;North-American Electric Reliability Corporation, 2016). However, research over the past decade has shown that this assumption is too simplistic and will cause a poor estimate of GIC during even modest storms (Beggan et al, 2013;Viljanen and Pirjola, 2017;Love et al, 2018;Blake et al, 2018;Sun and Balch, 2019). Hence, both the spatial and temporal pattern of the magnetic field and the underlying conductivity structure must be accounted for in order to produce realistic geoelectric field models over a wide region (Lucas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial variability of geoelectric fields is determined by non-uniformity of the geomagnetic field, combined with a nonlinear dependence on the 3D Earth's electrical conductivity structure. Even in the case of a 1D ground model, spatial variations of the magnetic field can produce a strongly non-uniform electric field (e.g., Viljanen et al 1999;Viljanen and Pirjola 2017). Vice versa, a realistic 3D ground conductivity model makes the electric field strongly non-uniform even when a plane-wave magnetic field is assumed (e.g., Bedrosian and Love 2015).…”
Section: Spatial Structure Of Geoelectric Fields and The "Smoothing Ementioning
confidence: 99%
“…A range of possible approaches may be applied to obtain the (a, b) parameters. The most common approach is to estimate these linear coefficients based on the power grid model (e.g., Viljanen et al 1999;Beggan et al 2013;Beggan 2015;Viljanen and Pirjola 2017). Other methods, particularly applicable in the absence of such information, but when selected GIC measurements are available, involve least-squares parameter estimation (e.g., Pulkkinen et al 2007;Ngwira et al 2008).…”
Section: Flavors Of Earth Conductivity Modeling Approachesmentioning
confidence: 99%